Form errors and topography after face milling with various machining parameters - Rybicki, M.; Kawalec, M. (НТУ "ХПИ", 2011)
In work the estimation of influence of conditions of cutting on a roughness of a surface of the tempered steel processed during face milling is presented. As variable conditions have accepted mainly depth of processing, submission and quantity edges of a face mill. It is confirmed, that milling with greater depth of processing, submission and quantity cutting edges leads to greater errors of the form of the processed surface. The finding homogeneous traces bidirectional not necessarily should testify to a greater plane of the processed surface than at the unidirectional traces.

In work the estimation of influence of conditions of cutting on a roughness of a surface of the tempered steel processed during face milling is presented. As variable conditions have accepted mainly depth of processing, submission and quantity edges of a face mill. It is confirmed, that milling with greater depth of processing, submission and quantity cutting edges leads to greater errors of the form of the processed surface. The finding homogeneous traces bidirectional not necessarily should testify to a greater plane of the processed surface than at the unidirectional traces.
Ошибки формы и топография после фрезерования с различными параметрами механической обработки
Keywords: tempered steel; face mill; processed surface; trace; закаленная сталь; торцевая фреза; обработанная поверхность